Penyuluhan dan Pemeriksaan Kesehatan Dalam Upaya Deteksi Dini Anemia Pada Anak-Anak Di Panti Asuhan Al-Hikmah Cangkringan, Sleman - Prasetya, Hieronymus Rayi (STIKES Yayasan RS.Dr.Soetomo, 2025)
Anemia is a condition in which the hemoglobin, a component in red blood cells, functions to bind oxygen and deliver it to all cells in the body so that they can carry out their functions properly. When you are anemic, your body feels weak and lethargic and gets tired easily, also known as 5L (Lethergic, Tired, Weak, Tired, Sluggish). Dizziness, cloudy eyes, and easy sleepiness accompany this. This community service aims to provide education and health checks to detect anemia early in children at the Al-Hikmah Cangkringan Orphanage, Sleman. The Methods of the study is four methods are used to implement community service activities: Target and Problem Surveys, Counseling on anemia, Health Checks (blood pressure, hemoglobin, and blood type checks), and Evaluation. The results of the study showed that examination of Hb levels in the children of Al-Hikmah Cangkringan Orphanage resulted in the category less than normal as much as 1 person (5%), normal as many as 17 people (90%) and the category above normal values as much as 1% (5%). Based on research results, most of the children at Al-Hikmah Orphanage are in the normal category and only 2 people need more supervision by the orphanage administrators.